Caracterização adaptativa de caprinos ibero-americanos - Silva, Wallace Sostene Tavares da (Universidade Federal Rural do Semi-Árido, 2014)
The objective of this study was to evaluate the adaptive responses of four groups of animals of different races: Majorera, Palmera, Canindé and Moxotó in winter and summer and dry and rainy season, intensively grown on the island of Tenerife - ES and extensively in the semi - arid respectively. Assuming the hypothesis that the animals present different adaptation mechanisms, since they evolved under the same environmental and management conditions. Hair characteristics such as: hair thickness (CT), average hair length (HL), mean diameter (DH) and number of hairs per cm2 numerical density (HN) were recorded. Some thermoregulatory responses such as rectal temperature (ºC), respiratory rate (breaths/min), surface temperature (ºC) and current respiratory volume and calorigenic hormone dosages, namely triiodothyronine (T3) and thyroxine (T4). As a way of evaluating homeostasis the biochemical profile of the animals was studied. The experimental period was performed in four herds for each breed, in 30 adult female caprines, in which the variation of these parameters was evaluated as a function of season or period of the year, shift and environmental variables. The environmental conditions of the Tenerife did not make the animals of the breed Majorera and Palmera if they vary their thermoregulatory responses, maintaining within their normal body temperature, the animals of the Palmera race show a greater sensitivity to the changes of temperature with the passage of the winter to the summer: 39.35 and 39.11 (RT, ⁰C); 32.12 and 48.58 (RR, breaths/min); 28.08 and 33.75 (ST, °C); 0.07 and 0.06 (vol/m2) respectively. These values were possibly influenced by the morphological characteristics of the pelage, which made it difficult to eliminate absorbed heat (20.03 and 13.05mm, 142.00 and 120.09 mm and 0.063 and 0.063 μm) when purchased from Majorera animals. According to the Principal Component Analysis (PCA), it can be observed that both races tended to trigger the FR more quickly and decrease the Vrc, mainly with the associated increase of Radiant Heat Load (RHL) and relative humidity, which confirms the adaptability of these animals to the environmental conditions of Tenerife. For animals of the Canindé and Moxotó breed in general, it was observed that the animals behaved differently by changes to the high values of air temperature (AirT) and Radiant Heat Load (RHL) associated to the high values of the Black Glob Humidit Index (BGHI) throughout the experimental period evidencing that in the rainy season, the season with the highest values for the environmental variable, the animals tended to increase their respiratory rate (RR), especially the Canindé breed when compared with (40.35 breaths/min vs 36.06 breaths/min, respectively). This behavior can be justified due to the high values of surface temperature (ST) within the same evaluated period (39.17 vs 37.24, respectively), justified by the black coloration of the Canindé breed and by the morphological characteristics of the fur that gave a greater capacity to absorb heat and di dissipates it. The Canindé breed presented a higher skin thickness (5.28mm), mean length (28.08mm) and hair density per cm2 (419.43 hair/cm2) than the Moxotó breed (4.27 mm; 85 mm, 347.03 hair/cm2), which made it difficult to exchange heat with the environment, but they were able to keep their rectal temperature constant
Keywords: adaptação; caprinos nativos; termorregulação; ilhas canarias; semiárido brasileiro; adaptation; native goats; thermoregulation; Canary Islands; semiarid region; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL